A vertical cavity surface emitting laser for CPT atomic clock. Issue 6 (30th March 2022) - Li, Ming; Wang, Qiuhua; Li, Yaobin; Qiu, Pingping; Meng, Hongling; Xie, Yiyang; Kan, Qiang
Abstract : A polarization-stabilized fundamental mode vertical cavity surface emitting laser (VCSEL) was developed for a coherent population trapping (CPT) Cs atomic clock. The VCSEL achieved a single stabilized polarization state through a directly-etched surface grating structure on the surface. The device polarization characteristics of different surface grating parameters were analysed using the finite-difference time-domain (FDTD) method. For the fundamental transverse mode condition, the lasing wavelength corresponded to the Cs atom's D1 line. Owing to the polarization-dependent reflectivity of surface gratings, the VCSEL's orthogonal polarization suppression ratio (OPSR) exceeded 20 dB. Since the surface grating eliminated the degeneracy of the two orthogonal linear polarization fundamental modes, a linewidth of approximately 53 MHz for the VCSEL could be obtained using the delayed self-homodyne method. A 7.6 GHz modulation bandwidth satisfied the atomic clock's bandwidth requirement. We introduced the directly-etched surface grating VCSEL to the Cs atomic clock, and measured the CPT resonance signal.